PERBANDINGAN KINERJA BERAHI KAMBING KACANG DAN KAMBING PERANAKAN ETAWAH (PE) YANG MENGALAMI INDUKSI BERAHI DENGAN PGF2 ALFA (Comparison of Estrous Performance between Kacang and PE Goats Following Estrous Induction with PGF2 Alpha) - Syafruddin Syafruddin; Juli Melia; Teuku Armansyah; Tongku Nizwan Siregar; Siti Rizki Hardyana Siregar; Ginta Riady; Dasrul Dasrul; Budianto Panjaitan; Hamdan Hamdan (Jurnal Medika Veterinaria, 2016)
The experiment was conducted to compare estrous performance between kacang and PE goats after estrous inducted with PGF2 alpha (PGF2α). Fifteen female goats were used in this study and divided into two groups. Characteristics of goat used are clinically healthy, never giving birth, 1,5-3,0 years of age, and have undergone at least two times the regular cycle. Group I (KI) consisted of 10 kacang goats and group II (KII) consisted of 5 PE goats. All goats in both groups were estrous synchronized with 1 ml PGF2a intramuscularly. Estrous observation was done visually three times a day at 8 a.m., 12 p.m., and 4 p.m. Assessment of estrous intensity based on scoring method. The data of intensity and onset were analyzed by Mann Whitney test and estrous duration analyzed by t test. The result showed that intensity, onset, and duration of estrous in KI vs KII were 2.47±0.21 vs 2.25±0.00, 38.20±2.39 vs 84.40±8.53 hours, and 40.40±2.27 vs 46.40±4.56 hours respectively. It concluded that there was different estrous performance between kacang and PE goats following estrous synchronized with PGF2α.